Assessment of chemotherapy‐induced peripheral neuropathy using the LDIFLARE technique: a novel technique to detect neural small fiber dysfunction. Issue 7 (26th May 2015) - Sharma, Sanjeev; Venkitaraman, Ramachandran; Vas, Prashanth R. J.; Rayman, Gerry
Abstract Introduction The diagnosis and quantification of chemotherapy‐induced peripheral neuropathy (CIPN) remains a challenge. Conventional methods including quantitative sensory testing (QST), nerve conduction tests, and biopsy are unable to detect subclinical changes, and do not consistently correlate with severity of patients' symptoms and functional impairment. This study aims to determine the utility of the LDI (laser Doppler imager) FLARE technique in the diagnosis of CIPN and whether it correlates with symptom severity. Materials and Methods We assessed 24 patients with established CIPN [12 due to platinum analogs (PA) and 12 to Taxanes (TX)] and 24 matched healthy controls (HC). All underwent neurophysiological examination including vibration perception threshold (VPT), sural nerve amplitude (SNAP) and conduction velocity (SNCV), LDIFLARE, and fasting biochemistry. The QLQ‐CIPN20 questionnaire was used to assess symptom severity. Results HC, combined chemotherapy (CG), PA, and TX groups were matched for age, sex, BMI, and blood pressure. The LDIFLARE was significantly reduced in CG compared to HC (P =< 0.0001), whereas SNAP (P = 0.058) and SNCV (P = 0.054) were not. The LDIFLARE correlated with the QLQ‐CIPN20 symptom scores in all three categories namely, CG (P =< 0.0001), PA (P = 0.001) and TX (P = 0.027) whilst, VPT, SNAP, and SNCV did not. Conclusion Our findings suggest that the LDIFLARE technique is more helpful in confirming the diagnosis of CIPN in patients with distal sensory symptoms than current commonly used methods. Moreover, this novel test fulfils the unmet need for a diagnostic test that relates to the severity of symptoms. This may be useful in quantifying early changes in small fibre function indicating early CIPN.